Automated Scheduling Algorithm Selection and Chunk Parameter Calculation in OpenMP - Mohammed, Ali; Korndorfer, Jonas H. Muller; Eleliemy, Ahmed; Ciorba, Florina M. (IEEE transactions on parallel and distributed systems, 2022)
Increasing node and cores-per-node counts in supercomputers render scheduling and load balancing critical for exploiting parallelism. OpenMP applications can achieve high performance via careful selection of scheduling kind and chunk parameters on a per-loop, per-application, and per-system basis from a portfolio of advanced scheduling algorithms (Korndörfer et al. , 2022). This selection approach is time-consuming, challenging, and may need to change during execution. We propose Auto4OMP , a novel approach for automated load balancing of OpenMP applications. With Auto4OMP, we introduce three scheduling algorithm selection methods and an expert-defined chunk parameter for OpenMP's schedule clause's kind and chunk , respectively. Auto4OMP extends the OpenMP schedule(auto) and chunk parameter implementation in LLVM's OpenMP runtime library to automatically select a scheduling algorithm and calculate a chunk parameter during execution. Loop characteristics are inferred in Auto4OMP from the loop execution over the application's time-steps. The experiments performed in this work show that Auto4OMP improves applications performance by up to 11% 11%<inline-graphic xlink:href="ciorba-ieq1-3189270.gif"/> compared to LLVM's schedule(auto) implementation and outperforms manual selection. Auto4OMP improves MPI+OpenMP applications performance by explicitly minimizing thread- and implicitly reducing process-load imbalance.